"Stickier" learning through gameplay: An effective approach to climate change education. Issue 2 (3rd April 2021) - Pfirman, S.; O'Garra, T.; Bachrach Simon, E.; Brunacini, J.; Reckien, D.; Lee, J. J.; Lukasiewicz, E.
Abstract: As the impacts of climate change grow, we need better ways to raise awareness and motivate action. Here we assess the effectiveness of an Arctic climate change card game in comparison with the more conventional approach of reading an illustrated article. In-person assessments with control/reading and treatment/game groups (N = 41), were followed four weeks later with a survey. The game was found to be as effective as the article in teaching content of the impacts of climate change over the short term, and was more effective than the article in long-term retention of new information. Game players also had higher levels of engagement and perceptions that they knew ways to help protect Arctic ecosystems. They were also more likely to recommend the game to friends or family than those in the control group were likely to recommend the article to friends or family. As we consider ways to broaden engagement with climate change, we should include games in our portfolio of approaches.